Apelin-13 Suppresses Neuroinflammation Against Cognitive Deficit in a Streptozotocin-Induced Rat Model of Alzheimer’s Disease Through Activation of BDNF-TrkB Signaling Pathway - Luo, Huaiqing; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Liu, Chi; Li, Guangyi; Han, Li; Qin, Xiaoqun (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD), a progressive neurodegenerative disease characterized by impairments of cognitive function as a result of synaptic deficits and neuronal loss, is associated with inflammation. Apelin-13, a predominant neuropeptide with inhibiting effect on inflammation, has beneficial effects on cognition memory and neuronal damage. However, whether apelin-13 can protect neurons to ameliorate cognitive deficits in AD by inhibiting the inflammatory response remains largely unknown. To test this hypothesis, rats were intracerebroventricularly (ICV) injected with streptozotocin (3 mg/kg) alone or in combination with apelin-13 (2 μg). And tyrosine receptor kinase B (TrkB) blocker K252a (200 nM) was administrated 10 min before apelin injection. Furthermore, cognitive performance was assessed by new object recognition (NOR) and Y-maze tests. Protein expression of apelin, APJ, microglial marker (IBA1), astroglia marker (GFAP), interleukin 1 beta (IL-1β), tumor necrosis factor-α (TNF-α), synaptophysin (SYP), brain-derived neurotrophic factor (BDNF), TrkB, phospho-TrkB (p-TrkB) in the hippocampus were examined by western blotting or immunohistochemistry. And the gene expression of IBA1, GFAP, IL-1β, TNF-α, and SYP were detected by real-time quantitative polymerase chain reaction (PCR). Inflammatory disorder in the hippocampus was tested by hematoxylin and eosin (H&E) staining. The enzyme-linked immunosorbent assay (ELISA) was used to study the expression level of acetylcholine. And the activity of acetylcholinesterase was detected by Acetylcholinesterase Assay Kit. We observed that apelin/APJ signaling was downregulated in the hippocampus of rats administrated with STZ. Apelin-13 was found to significantly ameliorate STZ-induced AD-like phenotypes including congnitive deficit, cholinergic disfunction and the damage of neuron and synaptic plasticity. Moreover, apelin-13 inhibited microglia and astrocyte activation, reduced IL-1β and TNF-α expression and hippocampal BDNF/TrkB expression deficit in AD rats. Finally, apelin-13-mediated effects were blocked by TrkB receptor antagonist K252a. These results suggest that apelin-13 upregulates BDNF/TrkB pathway against cognitive deficit in a STZ-induced rat model of sporadic AD by attenuating inflammation.